Genetic defects and calcium - Pozzan, Tullio (Henry Stewart Talks, 2007)
General concepts of calcium signaling, Mechanisms of calcium extrusion/uptake, Mechanisms of calcium release from the ER/SR, General concepts about plasma membrane calcium channels, Genetic defects of calcium release channels, Genetic defects of plasma membrane calcium channels, Genetic defects of calcium pumps, Novel findings on genetic defects of store dependent calcium channels